Development and the effectiveness of using fraction slider in solving higher order thinking skills word problems - Lavina Nair Madawan Nair (2021)
This study aims to develop and determine the effectiveness of the Fraction Slider in improving the performance of Year 5 students in solving Higher Order Thinking Skills (HOTS) addition and subtraction of fraction word problems. This study also aims to determine the effective problem solving strategy using the Fraction Slider. This study employed the design and development research (DDR) with a combination of quantitative and qualitative approach. In this study, DDR is limited to two phases; (1) Design and Development and (2) Evaluation. The first phase involved design and development of Fraction Slider using ADDIE Model. Three panel of experts were involved to validate the Fraction Slider using the expert opinion questionnaire. The percentage of experts agreement obtained was 87.9%. For the aspect of reliability, the Fraction Slider was used in teaching and learning for 27 students. Analysis of Cronbach alpha coefficient was calculated and obtained 0.82. The second phase employed a quasi- experimental design. It consists of 23 students for the control group and 25 students for the treatment group. The quantitative data was collected through pre-test and post-test. The study used Mann-Whitney test to show the significant difference between groups. The result showed that there is no differences between the control and treatment group in pre-test scores. There is a significant difference in the post- test between the two groups. Wilcoxon Signed Rank Test was used to compare the two related samples. This study revealed that there is no significant differences between the pre and post-test scores in solving the addition and subtraction of fractions in the control group. Next, there is a significant difference before and after being taught using the Fraction Slider for the treatment group. Qualitative descriptive research method was used to identify the problem solving strategy used by the students in solving word problems using the Fraction Slider. Qualitative data was collected via script analysis and task based interview. This study identified the Fraction Slider strategy to solve word problems effectively which was built upon existing idea of Polyas Model. In conclusion, the use of Fraction Slider strategy in teaching and learning HOTS Fraction word problem solving can significantly improve students performance. Accordingly, the Fraction Slider strategy is expected to assist teachers in enhancing the effectiveness of teaching and learning of word problems and help the students to acquire word problem solving skills.